Fabrication of functional and biodegradable scaffolds using nucleated poly(4-hydroxybutyrate) via 3D printing for bone tissue engineering. (15th January 2023) - Wang, Huaping; Cui, Jinyun; Li, Siting; Tao, Anmin; Du, Shanshan; Kan, Ze
Abstract: Poly (4-hydroxybutyrate) (P4HB) was a new generation of biosourced and biodegradable semi-crystalline polymer. However, due to the low crystallization temperature and slow crystallization rate of P4HB, there were problems such as insufficient cooling and product collapse during the 3D printing. The additive of biocompatible nucleating agents is one of the most effective means to promote the crystallization. Therefore, it was studied that the crystallization behavior and morphology of biodegradable P4HB were influenced by the zinc salt of d -phenylalanine (Zn(D-Phe)2 ) and cyanuric acid (CA) as efficient nucleating agents respectively. The addition of 2% Zn(D-Phe)2 and 0.6% CA could effectively increase the crystallization temperature, crystallization rate and nucleation density of P4HB spherulites, without damaging the crystal structure. Then, the bone tissue engineering scaffolds were prepared through 3D printing by the nucleated P4HB. The tensile strengths of P4HB/Zn(D-Phe)2 and P4HB/CA samples prepared by 3D printing were 33.4 MPa and 27.2 MPa, with the elongation at break of 449% and 370%, respectively, which fully met the requirements of bone tissue engineering on the mechanical properties of scaffolds. The results of biological property test showed that the P4HB were ideal scaffolds materials with good biological activity and biocompatibility. Highlights: Adopt chemical synthesized P4HB with excellent biodegradable and mechanical property. Promote the crystallization of P4HB by adding biocompatible nucleating agents. Construction a new P4HB scaffold by the 3D printing for bone tissue engineering. An ideal scaffolds material with good biological activity and biocompatibility.